The Black Hole - Poudel, Parashu Ram (Himalayan Physics, 2012)
Black holes are the cold remnants of former stars. They are so dense that no matter -not even light - is able to escape their powerful gravitational pull. These are interesting objects from a fundamental physics point of view and play an important role in astrophysics. The knowledge of phenomenon of origin of black hole may lead to new understanding of the nature of the real universe. The Himalayan Physics Vol. 3, No. 3 2012 Page : 50-55